MANAJEMEN PARENTING DALAM MENINGKATKAN HUBUNGAN SEKOLAH DENGAN ORANGTUA - Lindasari, Emi (Universitas Negeri Malang, 2017)
Abstract: The purpose of this research is to know the implementation of parentingmanagement to improve school public relation (a case study at SDI Surya Buana Malang).This research used the qualitative approach with case study design. The data collected byinterview, observation, and documentation. Categorizing the data was taken into accountas part of analsis process. This research founds that the implementation of parenting at SDISurya Buana Malang consists from planning, organizing, implementing, and evaluating.Keywords: parenting management, school and parent’s relationship.Abstrak: Tujuan penelitian ini untuk mengetahui manajemen parenting dalam meningkatkanhubungan antara sekolah dan orangtua di SDI Surya Buana Malang. Penelitian inimenggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Pengumpulan datamelalui wawancara, observasi, dan dokumentasi. Tahap analisis data dengan cara memilahmilahdata. Penelitian ini menemukan bahwa manajemen parenting di SDI Surya BuanaMalang terdiri dari perencanaan, pengorganisasian, pelaksanaan, dan evaluasi.Kata kunci: manajemen parenting, hubungan sekolah dan orangtua